The effect of porosity on fragmentation statistics of dynamically loaded ZrO2 ceramics - Marina Davydova; Sergei Uvarov; Oleg Naimark (Fracture and Structural Integrity)
The effect of load intensity and porous material structure on the fragmentation statistics of ZrO2(MgO)-based ceramics is studied. Cylindrical samples were fragmented under dynamic compression. Experimental data processing showed that the shape of stress-strain curves, the fragment size distribution and distribution of time intervals between the fractoluminiscense impulses depend on the sample porosity and load intensity. The X-ray Computed Tomography (CT) study of porous material structures allowed us to link the fragmentation statistics with pronounced porosity clustering (about 97% of the total pore volume) formed due to sintering.